FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN NYERI HAID (DISMENOREA) PADA SISWI MADRASAH ALIYAH NEGERI PASIR PENGARAIAN - Herawati, Rika (Jurnal Martenity and Neonatal, 2017)
Dysminorrhoea is pain in the lower abdominal area until pelvis while menstruating caused by the production of chemicals called prostaglandins which otherwise may increase menstrusi pain. Dysmenorrhoea experienced by many women in the united states estimated the prevalence 45 - 90% of dysmenorrhoea. The purpose of research known relationship early menarche, family history, duration of menstruation, menstrual cycle and regular exercise whit the incidence of dysmenorrhoea on students Madrasah Aliyah Negeri Pasir Pengaraian. This researche is a quantitative analytical research whit cross sectional study design, sample size 150 students Madrasah Aliyah Negeri Pasir Pengaraian, the sampling procedure sample by the total sampling, data collection using questionnaires and data analysis are univariat, bivariat whit chi – square. The results were obtained monstly experienced dysmenorrhoea 141 (94%). Variables associated whit the incidence of dysmenorrhoea is a family history (P = 0,002 < 0,05)S. The conclusion in this study is that there is a relationship between family history and incidence of dysmenorrhoea. Advice for a students is expected to better anticipated and be aware of the occurrence of anxiety dysmenorrhoea, then try to avoid and eliminate the factors that can affect the pain, such as stress and anxiety that often arise at the time before menstruations.